ON THE RHENIUM ACCUMULATION IN THE CARBONACEOUS-ILMENITIC METASOMATIC ROCKS AT PRIMOR'E - Tomson I.N.; Polyakova O.P.; Alekseev V.Yu. (My University, 2003)
A new type of rhenium accumulation, which is related to carbonaceous metasomatic rocks that are common in some ore fields at the Primor'e is described. Such metasomatic rocks are confined to shear and boudinage zones and to explosive breccia bodies. The process of metasomatic rock alteration accompanied the interaction of the ascending deeply generated flows of reduced hydrocarbon containing fluids with host rocks. The fluid flows transported a series of various metals including rhenium. The carbonaceous metasomatic rocks were sampled at the large Dalnegorsk ore field in Primor'e. The highest rhenium content in analyzed metasomatic rock samples reaches 0.7-1.5 ppm. Some recomendations are made for exploration of the metal-bearing carbonaceous facies of metasomatic rocks enriched with rhenium.